2016
DOI: 10.1002/ajpa.22895
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal craniofacial ontogeny in neandertals and modern humans

Abstract: Growth during adolescence appears to be fundamental in the expression of some Neandertal anatomies. Neandertal upper facial and nasal breadths appear to have expanded rapidly after puberty to account for differences between preadolescents and adults, and Neandertals and humans. Mandibular growth differences may relate to anterior tooth use to process foods and paramastication during Neandertal maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…therefore, it appears that occipital bun morphology was established by an early age. This observation complements the findings of Ponce de León and Zollikofer (2001) and Williams and Cofran (2016), who argued that many typical Neandertal traits appeared early in development, possibly even prenatally.…”
Section: The Fossil Connectionsupporting
confidence: 88%
See 2 more Smart Citations
“…therefore, it appears that occipital bun morphology was established by an early age. This observation complements the findings of Ponce de León and Zollikofer (2001) and Williams and Cofran (2016), who argued that many typical Neandertal traits appeared early in development, possibly even prenatally.…”
Section: The Fossil Connectionsupporting
confidence: 88%
“…Several previous studies found the ontogenetic trajectories of Neandertals and modern humans to be parallel (Krovitz, 2000;Ponce de León and Zollikofer, 2001;Ackerman and Krovitz, 2002;Zollikofer and Ponce de Leon, 2004;Freidline et al, 2012), while other studies found the postnatal trajectories of the two species to follow different slopes (Krovitz, 2003;Cobb and O'Higgins, 2004;Bastir et al, 2007;Zollikofer, 2012;Williams and Cofran, 2016). These studies all agree, however, that significant morphological differences between the two species are established early in developmenteither prenatally or very early in postnatal development.…”
Section: The Fossil Connectionmentioning
confidence: 55%
See 1 more Smart Citation
“…After some improvements over the years, the MMD turns out to be of wide use in anthropology when non-metric traits are used (Green, & Suchey, 1976;Rothhammer, Quevedo, Cocilovo, & Llop, 1984;Hanihara, Ishida, & Dodo, 2003;Sutter, & Mertz, 2004;Schillaci, Irish, & Wood, 2009;Williams, & Cofran, 2016). Furthermore, the use of non-metric traits and the MMD has been spread to other scientific field such as biology to study fauna (Sikorski,1982;Ansorge, 2001;Ansorge, Ranyuk, Kauhala, Kowalczyk & Stier, 2009), and even in informatics (Suryakan, & Mahara, 2016).…”
Section: Introductionmentioning
confidence: 99%